What are effective treatments for painful varicose veins?. Issue 11 (November 2015) - Manek, Megha; Kayes, Andrew; Sidhom, Michael; Gillan, Michael
Abstract : Evidence‐Based Answer : Compression stockings reduce symptoms more than placebo in patients with painful varicose veins who do not have ulcerations. Surgery, laser, and radiofrequency ablation appear to have similar effectiveness in symptom relief. Sclerotherapy appears to reduce symptoms more than compression stockings in pregnant patients (SOR: B, inconsistent or limited‐quality patient‐oriented evidence).